2019
DOI: 10.1111/jonm.12831
|View full text |Cite
|
Sign up to set email alerts
|

Association between nurses' breaks, missed nursing care and patient safety in Korean hospitals

Abstract: Aims: To examine the relationship between breaks and patient safety in Korean hospitals and determine the mediating effect of missed nursing care on this relationship. Background: Breaks during working hours can affect patient safety; however, few studies have examined the relationship between breaks and patient safety in hospitals and their findings were conflicting. Methods: A cross-sectional online survey was conducted with 399 nurses in Korean hospitals. Multiple linear regression was used to explore the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
55
0
10

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(69 citation statements)
references
References 39 publications
4
55
0
10
Order By: Relevance
“…However, care components stated to be missed most in the related literature may vary. For instance, a study conducted in Korea showed that the most missed MNC components were emotional support and full documentation of the necessary data (Min, Yoon, Hong, & Kim, 2019). This is assumed to be associated with varied nursing care policies across countries or institutions.…”
Section: Discussionmentioning
confidence: 99%
“…However, care components stated to be missed most in the related literature may vary. For instance, a study conducted in Korea showed that the most missed MNC components were emotional support and full documentation of the necessary data (Min, Yoon, Hong, & Kim, 2019). This is assumed to be associated with varied nursing care policies across countries or institutions.…”
Section: Discussionmentioning
confidence: 99%
“…An actual response rate could not be estimated because the number of nurses who saw the advertisement in the mobile application was unknown. A total of 618 nurses consented to participate in the survey, and 126 nurses did not complete it (nonresponse rate: 20.38%; Min, Yoon, Hong, & Kim, 2019). Therefore, 492 nurses completed the survey, and 488 (effective response rate: 99.19%) valid responses were used in the final analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Nurses’ occupational fatigue was measured using the Korean version of the Occupational Fatigue Exhaustion/Recovery (OFER‐K) scale (Min et al, 2019). The OFER‐K scale consists of 15 items divided equally into three subscales: acute fatigue (OFER‐AF), inter‐shift recovery (OFER‐IR), and chronic fatigue (OFER‐CF).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A paper reported that 75% of nurses reported missing at least one activity, and 55%-98% reported at least one task undone (Min, Yoon, Hong, & Kim, 2019). These missing activities are closely associated with lower patient safety, including increased nosocomial infection, pressure injuries, medication errors and increased patient admissions and readmissions.…”
Section: Compromised Hospital Carementioning
confidence: 99%